2021
DOI: 10.1002/casp.2580
|View full text |Cite
|
Sign up to set email alerts
|

Collective disadvantage in the context of socioeconomic crisis in Greece: The role of system‐directed anger, politicians‐directed anger and hope in normative and non‐normative collective action participation

Abstract: Group-based anger might take different forms depending on the target that is directed at. In this research, conducted in Greece (N = 470), we distinguished between two types of group-based anger in the context of socioeconomic crisis: Anger directed towards the international system and anger directed towards the local politicians. We showed that politicians-directed anger is better predicted by the mere perception of collective disadvantage, whereas system-directed anger by the perceived illegitimacy of disadv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…It seems that people want to restore their sense of power through any form of action that they consider valid; individual activity via engagement in politics and via nonnormative collective action. We should note that our findings may reflect an inclination to express anger toward politicians and the political system, more broadly, and other forms of nonnormative collective action in contexts of collective disadvantage, where normative collective actions often also decrease (e.g., Petkanopoulou et al, 2021). Blaming powerful agents and elected representatives may involve responsibility attribution and expression of anger or other—often considered as illegitimate—forms of action (Iyer et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…It seems that people want to restore their sense of power through any form of action that they consider valid; individual activity via engagement in politics and via nonnormative collective action. We should note that our findings may reflect an inclination to express anger toward politicians and the political system, more broadly, and other forms of nonnormative collective action in contexts of collective disadvantage, where normative collective actions often also decrease (e.g., Petkanopoulou et al, 2021). Blaming powerful agents and elected representatives may involve responsibility attribution and expression of anger or other—often considered as illegitimate—forms of action (Iyer et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…While non-confrontational collective action research examines daily life injustice and deprivation experiences of diverse groups, confrontational collective action research mostly focuses on the role of injustice in historically oppressed groups' collective action in the context of protracted conflicts such as Spain and Israel (e.g., Hasan-Aslih et al, 2019;Lobato et al, 2020;Saguy et al, 2020;Shuman et al, 2016). Relatedly, collective anger emerges as one of the most important antecedents of both confrontational and non-confrontational collective actions (Obaidi et al, 2018;Petkanopoulou et al, 2022;Wohl et al, 2014), whereas contempt and hatred are seen as emotional triggers of mostly confrontational collective actions (e.g., Becker, Tausch, & Wagner, 2011;Hasan-Aslih et al, 2019;Morales et al, 2020;Tausch et al, 2011). However, more studies are needed for the emotional mapping of confrontational collective action.…”
Section: Discussionmentioning
confidence: 99%
“…Karampampas et al (2020) showed that participants with higher levels of anger are significantly more likely to have committed confrontational political acts (e.g., 'using personal violence against the police or damaging property') across nine European countries. Petkanopoulou et al (2022) distinguished and tested the role of anger towards international system vs local politicians on confrontational (e.g., 'occupy public buildings, take part in riots with police') versus non-confrontational (e.g., 'go on strike, join a trade union') collective actions during socio-economic crisis in Greece. Perceived illegitimacy was positively associated with both confrontational and non-confrontational collective actions through system-directed anger, while anger towards local politicians did not predict either type of action.…”
Section: Emotional Factorsmentioning
confidence: 99%